PENYELESAIAN SENGKETA TERHADAP OBLIGASI KORPORASI YANG DINYATAKAN PAILIT OLEH PENGADILAN NIAGA (Solusi, 2024)
Law of the Republic of Indonesia Number 8 of 1995 concerning capital markets contains bonds which are also regulated in article 1 number 3 of the Minister of Finance Regulation Number 27 of 2020 where bonds are Government Debt Securities (SUN) with a term of more than one year with a coupon. and plus limited interest installments (discounts). Bonds can also be interpreted as liability protection provided by the bond issuer to investors, accompanied by an agreement to replace the principal obligation along with the premium coupon at a predetermined time. Interestingly, regarding these bonds where the company responsible or the issuer is declared bankrupt, what is the settlement system? Settlements within the scope of the security services sector are known as other international settlements which are carried out by means of litigation through the Courts in which the Criminal Procedure Case is implemented.